FEATURES OF ECHOMETRY PARAMETERS OVARIES IN DIFFERENT PHASES OF THE MENSTRUAL CYCLE GIRLS WITH DIFFERENT SOMATOTYPE - Черкасова, Л.А. (World of Medicine and Biology, 2014)
In 78 healthy urban girls of Podillya with different somatotype between the ages of 16 and 18 percentile scope boundary and features echometry size of ovaries in different phases of the menstrual cycle (MC) were defined. Found that girls with different somatotypes the largest number of statistically significant differences in the size of ovarian ultrasound determined during the luteal phase and follicular - all sizes significantly larger and tend to have higher values in patients with endo-mesomorphic somatotype than in girls with other somatotype. In representatives of most ovarian sizes tend to lower values during follicular phase of MC than during ovulation and (or) luteal phase of MC (size of the ovary during follicular phase
Keywords: echometric indicators of ovarian; somatotype; menstrual cycle; healthy girl